Investigação da Atividade Antifúngica do Óleo Essencial de Eugenia caryophyllata Thunb. sobre cepas de Candida tropicalis - Mendes, Juliana Moura (2011)
The candidiasis is a fungal opportunistic infections involving Candida. In Brazil, the specie C. tropicalis is the second most commonly isolated after C. albicans. The emergence of strains resistant to conventional antifungal agents has increased the search for new alternatives from natural products, especially essential oils. This study investigated the activity of essential oil (EO) Eugenia caryophyllata Thunb.(clove) on strains of C. tropicalis by Minimum Inhibitory Concentration (MIC), Minimum Fungicidal Concentration (MFC), Micromorphology, fungal viability (time-kill) and checkerboard. The CIM and CFM were respectively 512 and 1024 μg/mL for the essential oil and 2 μg/mL for amphotericin B. When we evaluated the action of OE and amphotericin B on the morphology of the clinical strain, we observed inhibition of the formation of hyphae and pseudohyphae, which are important virulence factors in the development of candidiasis. There was also the essential oil has a concentration-dependent antifungal activity and that the association of OE and amphotericin B demonstrated effect additive. Given this, it is concluded that the essential oil of E. caryophyllata showed a strong inhibitory activity against C.tropicalis and thus can be considered as a potential product with antifungal properties, especially for the treatment of candidiasis.